Trends and prescribing patterns of oral anti-neoplastic drugs: a retrospective longitudinal study - Lv, Xiaoqun; Ren, Weifang; Ran, Shan; Zhao, Yuhan; Zhang, Jihong; Chen, Jun; Zhang, Ning (Frontiers in Public Health, 2023)
Background: Cancer as a global public health problem, imposes a heavy disease burden. With the rapid development of oral anti-neoplastic drugs, there has been a paradigm shift in the treatment of cancer from intravenous to oral administration. Objective: This study was conducted to investigate the trends and prescribing patterns of oral anti-neoplastic drugs in an academic tertiary hospital in China. Methods: A single-center and retrospective analysis was performed based on the prescriptions of outpatients treated with oral anti-neoplastic drugs from2017 to 2022. Yearly prescriptions and expenditure were calculated according to their pharmacological classes, and trends were further analyzed. Defined daily doses (DDDs) and defined daily cost (DDC) of oral targeted anti-neoplastic drugs were also determined Results: Both the number of prescriptions and expenditure of oral anti-neoplastic drugs increased progressively. There was a significant upward trend in the number and proportion of prescriptions for the elderly group, male group, and patients with gynecologic/genitourinary and respiratory cancer. Hormonal therapy agents accounted for the highest proportion of prescriptions, and letrozole was initially the most frequently prescribed drug. The number of DDDs of total oral targeted anti-neoplastic drugs showed a continuously ascending trend, primarily driven by the usage of epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) and BCR-ABL TKIs. Conclusion: The prescriptions and expenditure of oral anti-neoplastic drugs, and the number of DDDs of oral targeted anti-neoplastic drugs all showed a progressively ascending trend. Further studies are needed to evaluate the long-term health and financial outcomes, and the factors influencing these prescribing patterns.